2015
DOI: 10.4238/2015.august.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and effects of miR-21 expression in esophageal cancer

Abstract: ABSTRACT. The aim of this study was to investigate the expression of miR-21 in esophageal cancer and the impact of miR-21 on apoptosis, invasion, and the expression of target genes in esophageal cancer cells. Fluorescence quantitative polymerase chain reaction analysis was used to detect the expression of miR-21 in human esophageal tissues, adjacent tissues, and an esophageal cancer cell line (TE-13). The antisense miR-21 oligonucleotide was generated commercially using the solidphase chemical synthesis method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 16 publications
2
21
0
1
Order By: Relevance
“…The up-regulation of miR-21 can predict an unfavorable prognosis in ESCA, as confirmed by three independent meta-analyses [3032]. Several studies also found that the up-regulation of miRNA-21 could serve as a potential diagnostic biomarker [33–36], which is consistent with our result using TCGA data.…”
Section: Discussionsupporting
confidence: 90%
“…The up-regulation of miR-21 can predict an unfavorable prognosis in ESCA, as confirmed by three independent meta-analyses [3032]. Several studies also found that the up-regulation of miRNA-21 could serve as a potential diagnostic biomarker [33–36], which is consistent with our result using TCGA data.…”
Section: Discussionsupporting
confidence: 90%
“…MiR‐21 expression in EC tissues in patients with lymph node metastasis was significantly higher than in patients without lymph node metastasis. The results also showed that high miR‐21 expression in TE‐13 cells increased cell proliferation and invasion and inhibited apoptosis …”
Section: Introductionmentioning
confidence: 90%
“…The results also showed that high miR-21 expression in TE-13 cells increased cell proliferation and invasion and inhibited apoptosis. 22 Komatsu et al conducted in vivo testing to ascertain whether oncogenic miR-21 promoted chemoresistance in EC patients and acted as a biomarker for predicting chemoresistance in plasma from patients with EC. All EC patients were treated with a preoperative chemotherapy regimen of cisplatin plus 5-fluorouracil (5-FU).…”
Section: Zn Deficiency Affects the Development Of Ec By Regulating MImentioning
confidence: 99%
“…Of these, miR-124 has been reported to be important in a variety of cancers (Cao et al, 2007;Visvanathan et al, 2007). Wen et al (2015) reported that miR-21 might be involved in the development and metastasis of esophageal cancer through its interaction with target genes programmed cell death 4 (PDCD4) and K-ras. Deng et al (2013) showed that overexpression of CDK4 results in a poorer prognosis and confers resistance of glioma cells to radiation.…”
Section: Discussionmentioning
confidence: 99%